An epidemiologic survey on the causes of infertility in patients referred to infertility center in Fatemieh Hospital in Hamadan - Seyedeh Zahra Masoumi; Parisa Parsa; Nooshin Darvish; Sahar Mokhtari; Mahnaz Yavangi; Ghodratollah Roshanaei (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Infertility is considered as a major health care problem of different communities. The high prevalence of this issue doubled its importance. A significant proportion of infertility have been related to environmental conditions and also acquired risk factors. Different environmental conditions emphasized the need to study the different causes of infertility in each area. Objective: The aim of this study was to determine the frequency causes of infertility in infertile couples. Materials and Methods: In this cross sectional descriptive study 1200 infertile men and women that were referred to infertility clinic of Fatemieh Hospital during 2010 to 2011, were examined. This center is the only governmental center for infertility in Hamadan. Sampling was based on census method. Information about the patients was obtained from medical examinations and laboratory findings. To analyze the data, descriptive statistics such as frequencies and the mean were used. Results: The prevalence of primary and secondary infertility was 69.5% and 30.5% respectively. Among the various causes of infertility women factors (88.6%) had the highest regard. In the causes of female infertility, menstrual disorders, diseases (obesity, thyroid diseases, and diabetes), ovulation dysfunction, uterine factor, fallopian tubes and cervical factor had the highest prevalence respectively. The causes of male infertility based on their frequency included semen fluid abnormalities, genetic factors, vascular abnormalities, and anti-spermatogenesis factors, respectively. Conclusion: Etiology pattern of infertility in our study is similar with the many other patterns that have been reported by the World Health Organization. However, frequency of menstrual disorders is much higher than other studies that require further consideration.